2020
DOI: 10.1177/0961203320909156
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory characteristics in juvenile-onset systemic lupus erythematosus across age groups

Abstract: Background Systemic lupus erythematous (SLE) is a systemic autoimmune/inflammatory condition. Approximately 15–20% of patients develop symptoms before their 18th birthday and are diagnosed with juvenile-onset SLE (JSLE). Gender distribution, clinical presentation, disease courses and outcomes vary significantly between JSLE patients and individuals with adult-onset SLE. This study aimed to identify age-specific clinical and/or serological patterns in JSLE patients enrolled to the UK JSLE Cohort Study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 23 publications
8
72
0
10
Order By: Relevance
“…The youngest patient group less frequently presented with leukopenia ( p = 0.002), thrombocytopenia ( p = 0.004) and/or low complement ( p = 0.002) when compared to older age groups. The present study supports the hypothesis that patients diagnosed with jSLE during adolescence may display a more ‘classic’ SLE phenotype due to variation in the pathogenic mechanisms at different ages, accounting for the more atypical SLE presentation seen in younger patients [ 20 ].…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…The youngest patient group less frequently presented with leukopenia ( p = 0.002), thrombocytopenia ( p = 0.004) and/or low complement ( p = 0.002) when compared to older age groups. The present study supports the hypothesis that patients diagnosed with jSLE during adolescence may display a more ‘classic’ SLE phenotype due to variation in the pathogenic mechanisms at different ages, accounting for the more atypical SLE presentation seen in younger patients [ 20 ].…”
Section: Introductionsupporting
confidence: 87%
“…The study also showed that Black African/Caribbean jSLE patients exhibit more renal involvement and more frequently receive cyclophosphamide and rituximab during their disease course when compared to patients of other ethnicities. Similar to adult studies, jSLE was found to be more prevalent in patients from minority ethnic backgrounds, compared to the UK national census figures for prevalence of ethnic minorities in the population as a whole, with 51% of UK jSLE Cohort Study participants being Caucasian, compared with 86% of the UK population as a whole [29]. Of interest, the present study also showed higher numbers of male patients and less ANA and/or anti-dsDNA positivity among Caucasians (as compared to patients from minority ethnic backgrounds), which may be due to the presence of more 'atypical' and/or 'monogenic' disease in Caucasians [2,4,29].…”
Section: Impact Of Age On Disease Presentationsupporting
confidence: 61%
See 1 more Smart Citation
“…The onset of cSLE is reported to peak during the peri-pubertal years with a median age of onset between 11–12 years and the disease is rare under the age of 5 years [ 20 ]. In SEA, ( Table 1 ) most patients are diagnosed between the ages of 11–13 years, which is comparable with other multiethnic cohorts in the West.…”
Section: Epidemiology and Demographicsmentioning
confidence: 99%
“…In recent years, Th cell subsets and cytokines have been found to play an important role in the pathogenesis of SLE [9]. cSLE is often more serious than that in adults, as the probability that each organ is involved is higher, and the disease process is more dangerous than that in adults [10,11]. Therefore, the detection of cytokines in SLE patients is helpful to comprehensively understand the immune status of the body and correctly judge disease condition.…”
Section: Introductionmentioning
confidence: 99%